ACTIVITY ESTIMATION WHEN DEALING WITH COLLECTIONS OF URANIFEROUS MINERALS. Issue 3 (23rd February 2022) - Fedeli, Luca; Doria, Sandra; Moggi Cecchi, Vanni; Cupparo, Ilaria; Fabrizi, Lucilla; Gori, Cesare
Abstract: The activity estimation of hand-size specimens of uraniferous minerals is not a trivial issue due to the manipulation difficulty caused by the emitted ionising radiation and the dependence of radiometric quantities from several parameters. Sample modelling requires approximations, leading to large uncertainty in the evaluation of the activity. In this work, a new procedure to evaluate uraniferous specimens activity, including a detailed description of measured parameters, the instrumentation and the mathematical formulation of the process, is presented. The proposed methodology takes into consideration sample size, ore composition and measured radiation. The procedure was used to measure the activity of a group of uraniferous mineral specimens belonging to Natural History Museum of the University of Florence, Italy. The experimental set-up was designed to reduce the measurement uncertainty. The aim of this work is to propose a methodology that can be easily applied to the specimens manipulation, conservation and exhibition.